스마트폰 이미지와 인공지능 기반 분석 기법을 활용한 솔잎혹파리 피해 평가 연구 - 임원택; Wontaek Lim; 정누리; Nuri Chung; 장병우; Byungwoo Chang; 고찬우; Chanwoo Ko; 남영우; Youngwoo Nam; 고동욱; Dongwook W. Ko (한국산림과학회지, 2025)
본 연구는 소나무(Pinus densiflora)와 곰솔(P. thunbergii)에 피해를 주는 해충인 솔잎혹파리(Thecodiplosis japonensis)의 관리 의사결정에 필요한 예찰 정보를 효율적으로 수집하기 위한 방법으로 스마트폰 이미지와 인공지능 기반 이미지 분석 모델의 활용 가능성을 평가하였다. 이를 위해 솔잎혹파리 피해 시료와 스마트폰 이미지를 수집하였고, 시료로부터 실측한 피해 정보는 인공지능 기반 이미지 분석 모델의 학습과 검증을 위한 종속변수로 활용하였다. 인공지능 모델의 학습은 제한된 자료의 효율적인 활용과 일반성 확보를 위해 전이학습(transfer learning)과 이미지 증강(augmentation) 기법을 적용하였으며, 전이학습을 위한 모델로 ResNet-18과 사전 학습된 가중치를 이용하였고 학습자료에는 증강 기법을 적용하여 색상과 기하학적 다양성을 확보하였다. 최종 학습된 모델은 충영형성률 분석에서 RMSE 4.05, 결정계수(R 2 ) 0.98의 높은 성능을 보였으며, 이를 기반으로 분류한 피해도 또한 정확도 0.92, Cohen's Kappa 0.88의 높은 일치율을 나타냈다. 그러나 일부 시료 유형에서 인식 오류가 관찰되었으며, 현장에서 활용하기 위해서는 학습자료의 다양성을 확보를 통한 모델의 일반성 개선이 필요하다는 것을 의미한다. 향후에는 기주 수종 간 피해증상 및 저항성 차이, 형태적 변이, 예찰 시기에 따른 피해증상 변화, 다른 병해충에 의한 피해 등 다양한 요인을 고려한 학습자료를 확보함으로써, 전국 규모의 예찰에 적용 가능한 솔잎혹파리 피해 분석 모델로 확장될 수 있을 것으로 기대된다. 본 연구는 솔잎혹파리 예찰의 효율성 향상을 위한 방법론을 제시하였으며, 해당 방법론은 다양한 산림병해충의 효율적인 예찰 체계를 확립하기 위해 활용할 수 있을 것으로 기대된다. The pine needle gall midge (Thecodiplosis japonensis) is an invasive pest that poses a serious threat to Korean red pine (Pinus densiflora) and black pine (P. thunbergii) in Korean forests. This study evaluated the potential application of artificial intelligence (AI) models to analyzing images taken by smartphones for the damage caused by the pine needle gall midge to aid in monitoring and management efforts. Smartphone images were taken of damaged first-year shoots, which were then collected to measure data such as the gall formation rate (GFR) and severity level (SL) for model training and validation. To mitigate the limitations of the dataset and enhance generalizability, transfer learning was applied using the ResNet-18 architecture with pretrained weights, and the training data were augmented to increase the variability in terms of color and geometric characteristics. The final model predicted the GFR with high accuracy by achieving an RMSE of 4.05 and R 2 of 0.98. The SL was also predicted well with an accuracy of 0.92 and Cohen's kappa of 0.88. Some inconsistencies in the prediction performance were observed that were likely due to the limited diversity of the training data. More training data are needed that account for variations in the symptoms and resistance of the host species, morphological traits within species, symptoms in different phases, and overlapping damage from other pests. The developed AI-based methodology is expected to enhance the efficiency of monitoring systems at tracking the pine needle gall midge and other forest pests.